Notarial Liability for Changes in the Shareholder Composition of Limited Liability Companies - Irba Ufairah Razak (Punggawa Legacy Center, 2026)
Changes in the shareholder composition of a limited liability company are not merely internal administrative adjustments. They affect voting power, dividend entitlement, control, beneficial ownership, corporate governance, and the legitimacy of subsequent corporate decisions. In Indonesian practice, such changes commonly arise from share transfers, capital increases, acquisitions, inheritance, conversion of company status, or restructuring of ownership. This article examines the responsibility of notaries in drafting deeds, verifying corporate documents, ensuring the legality of shareholder resolutions, and submitting changes through the electronic legal entity administration system. Using normative research, this article argues that notaries are not absolute guarantors of hidden material facts, but they remain responsible for formal legality, prudence, neutrality, accurate deed-making, document consistency, and accountable electronic filing.